PEMANFAATAN LIMBAH TULANG IKAN TONGKOL(Euthynnus affinis)UNTUK PEMBUATAN STIK DENGAN PENAMBAHAN DAUN KALE (Brassica oleracea L.) SEBAGAI PEWARNA ALAMI DAN MENINGKATKAN IMUN - Arifky Hidayatullah (AGROTERAP : Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2021)
Sticks are long, flat cakes that have a savory taste and crunchy texture that are processed by frying or baking. Tuna is a type of marine fish that has a high nutritional content and is good for consumption. Kale leaf or Brassica Oleracea L is a vegetable that has very high nutritional value, especially vitamin C. This study aims to determine the level of preference for tuna fish bone meal sticks with the addition of kale leaf extract as a natural dye. This study used the following combination treatments: P0 (Without Addition of Tuna Fish Bone Flour and Kale Leaf Extract), P1 (15% Tuna Fish Bone Flour and 10% Kale Leaf Extract), P2 (20% Tuna Fish Bone Flour and 15% Kale Leaf Extract), P3 (25% Tuna Fish Bone Flour and 20% Kale Leaf Extract). The stick product was tested on 30 untrained panelists on the aspects tested, namely preference, taste, aroma, color and texture using 5 scales. The results showed that the sticks with the addition of tuna bone meal and kale leaf extract had an effect on the organoleptic characteristics. The panelist's level of preference stated that he liked the P2 treatment and got the highest score of 43%. The organoleptic test of the level of taste and texture preference obtained the highest score on the panelist assessment stating that they liked the P0 treatment by 40% and P0 by 43%. The organoleptic test of the level of preference for aroma and color obtained the highest score on the panelist assessment stating that they liked the P2 treatment by 40% and P2 by 53%. The results of the sticks with the best formula were in the P2 treatment (20% Tuna Fish Bone Flour and 15% Kale Leaf Extract).